Association between Habitual Dietary Salt Intake and Risk of Gastric Cancer: A Systematic Review of Observational Studies. (22nd October 2012) - Ge, Sheng; Feng, Xiaohui; Shen, Li; Wei, Zhanying; Zhu, Qiankun; Sun, Juan
Abstract : Purpose. Systematic reviews of case-control and prospective studies showed a positive association between habitual salt intake and gastric cancer. Given new studies published thereafter, we carried out a meta-analysis to assess the association between dietary salt intake and gastric cancer. Methods. Case-control studies and cohort studies published between January 1992 and January 2012 on PubMed and Embase were searched. We quantified associations between salt intake and gastric cancer with meta-analysis. Results. Eleven studies (7 case controls and 4 cohorts) finally were included in the meta-analysis (total population: n = 2076498 ; events: n = 12039 ). The combined odds ratio showed significantly positive association between high salt intake and gastric cancer compared with low salt intake (OR = 2.05, 95% CI [1.60, 2.62]; P < 0.00001 ). In subgroup meta-analysis, findings were slightly different when analyses were restricted to salty food intake (OR = 2.41, 95% CI [2.08, 2.78]; P < 0.00001 ) as well as in Asia (OR = 1.27 95% CI [1.22, 1.32]; P < 0.00001 ). There was no evidence that sample size, exposure assessment substantially influenced the estimate of effects. Conclusions. The systemic review supports the hypothesis that dietary salt intake is positively associated with the risk of gastric cancer.